Strengthening Public Education by Implementing RTE - Kasinathan, Gurumurthy (Voices of Teachers and Teacher Educators, 2019)
There is a decline in enrollment in government schools in many states in India and increase in enrollment in private schools, this is partly due to a migration of students from government schools to private schools. However, this shift leads to increasing stratification of school education, which is an obstacle to social mobility. One way of addressing this stratification, as well as improve quality of school education in India, is to implement the RTE in letter and spirit. This will require the government to shut down private schools which do not meet the requirements of RTE with respect to infrastructure and teacher provisioning. The Central and state governments will also significantly increase their budgetary investment on government and aided schools to ensure they meet these RTE norms. Governments also need to invest in greater school – community linkages to strengthen government school accountability to the local community. Such increase in investment is also required to meet the norm of 6% of GDP investment in education, suggested by the Kothari Commission report of 1966.